Durability of Modified Expanded Polystyrene Concrete after Dynamic Cyclic Loading. (6th January 2016) - Shi, Wenbo; Miao, Linchang; Luo, Junhui; Wang, Jiaqi; Chen, Yinan
Abstract : EPS concrete was produced by mixing the expanded polystyrene spheres (EPS) and polymer emulsion and thickener to the matrix concrete, and this concrete had good vibration energy absorption characteristics. Based on the experimental data obtained on EPS volume ratio of 0%, 20%, 30%, and 40% by replacing matrix or coarse aggregate, the two design styles had nearly the same compressive strength. By applying frequency of 5 Hz, 50000 or 100000 times, 40 KN, 50 KN, and 60 KN cyclic loading, it is shown that the higher the inclusion size was, the lower the compressive strength of the EPS concrete would be; the larger the applying dynamic cyclic load was, the more obvious the compressive strength changing would be. Meanwhile, the strength of EPS concrete had no evident change after durability test. The results of this research had practical significance on using EPS concrete in some long-term cyclic dynamic load engineering.